(untitled) (Bangladesh Journal of Medical Education, 2017)
This cross sectional descriptive study was conducted among the health policy makers, health administrators, doctors including medical teachers, intern doctors, clinically exposed medical students and patients. The study was conducted at government and non government medical colleges of Dhaka and outside Dhaka from 1st July 2014 to 30th June 2015. Total respondents were 372 and information was collected through in-depth interview schedule and self administered semi structured questionnaire. The qualitative information was collected from health policy makers including administrators by in-depth interview which was complimentary to the findings obtained by self administered semi structured questionnaire. Out of 372 respondents 280 (75.3%) and 92 (24.7%) were engaged in government and non- government hospitals/ organizations respectively. Among the respondents 164 (44.1%) agreed and 98 (26.3%) strongly agreed that introduction of licensing examination for the medical and dental practitioners are justified in the present context of Bangladesh. Of the total, 294 (79%) agreed and 40 (10.8%) strongly agreed that licensing examination shall be useful for individual professional development and also agreed that this will help in overall professional development, shall improvement of professional competency and shall enrich doctors with updated professional knowledge. Majority of the respondents (70.6%) mentioned that doctors may not be interested. Of the same respondents 99.1% opined that the registration shall be on the basis of degree or the examination shall only be for person graduated from abroad or foreigner graduates. About 73% respondents were in agreement with 5 years validity period for an examination. Of the total 84.4% respondents agreed that the examination will improvement of standard of medical and dental education offered by all medical and dental colleges of Bangladesh. There are many direct and indirect benefits of introducing licensing examination for the registration of medical and dental graduates/practitioners and there are a few barriers to implement that too. Bangladesh Journal of Medical Education Vol.8(1) 2017: 2-8